Distribution and abundance of carangidae (Teleostei, Perciformes) associated with oceanographic factors along the northeast brazilian exclusive economic zone - Christiane Sampaio de Souza (Brazilian Archives of Biology and Technology, 2008)
This work had as objective to study the distribution and abundance of the Carangidae larvae and to analyze the influence of the hydrological (temperature and salinity) and biological factors (phytoplanktonic biomass and zooplanktonic biomass), on the space and temporal distribution of the larvae. Ichthyoplankton was collected during four expeditions from the Northeast Exclusive Economic Zone. Six species (Trachurus lathami, Decapterus punctatus, Chloroscombrus chrysurus, Selene setapinnis, Selene vomer and Elagatis bipinnulata) and Caranx- Carangoides complex were identified. D. punctatus was the species most abundant (52% of the total), with higher abundance during the Period 3, while the Period 2 was the period of low abundance. C. chrysurus was the second species in abundance representing 30% of the total of carangid. This species had higher abundance during the Period 2 and the Period 1. However, in Period 3 abundance were lesser. The third species in abundance was T. lathami that corresponded 8% of the total of carangid larvae. S. setapinnis, S. vomer and E. bipinnulata were the species less abundant, representing together 2% of the total identified larvae. The larvae of Caranx- Carangoides complex represented 9% of the carangid total. Este trabalho teve como objetivo estudar a distribuição e abundância das larvas de Carangidae, foi analisada também a influência de fatores hidrológicos (temperatura e salinidade) e biológicos (biomassa fitoplanctônica e biomassa zooplanctônica), sobre a distribuição espacial e temporal dessas larvas. O ictioplâncton foi coletado durante quatro expedições: Período 1 (Agosto Outubro 1995), Período 2 (Janeiro Abril 1997), Período 3 (Abril Julho 1998) e Período 4 (Setembro Dezembro 2000)), realizadas na Zona Econômica Exclusiva do nordeste. Em um total de 313 larvas foram identificadas 6 espécies (Trachurus lathami, Decapterus punctatus, Chloroscombrus chrysurus, Selene setapinnis, Selene vomer e Elagatis bipinnulata) e o Complexo Caranx Carangoides pertencentes à família Carangidae. D. punctatus foi a espécie mais abundante neste estudo (52% do total). Sua maior abundância foi observada no Período 3 e a menor no Período 2. C. chrysurus foi a segunda espécie em abundância representando 30% do total de carangídeos. Esta espécie teve maior abundância durante o Período 2, enquanto que os Períodos 1 e 3 foram ás épocas de menor abundância. A terceira espécie em abundância foi T. lathami que correspondeu 8% do total de larvas de carangídeos, sendo o Período 4 o mais abundante. S. setapinnis, S. vomer e E. bipinnulata foram bem menos abundantes que as outras espécies analisadas, representando juntas 2% do total de larvas identificadas. Larvas do Complexo Caranx - Carangoides representaram 9% do total de carangídeos.